Studi Eksperimental Pengaruh Bukaan Katup Inlet dan Outlet Ring Blower RB-200S - Novarini; Dhany Murtono; Ahmad Imam Rifa’i (LPPM Politeknik Jambi, 2021)
The blower is a device used to increase the air pressure and increase the flow rate of air and gas. In this study, the effect of the inlet and outlet valve openings of the ring blower was experimentally investigated. Variations in the inlet and outlet valve openings are 50%, 75%, and 100%, respectively. The results showed that the larger the opening of the inlet and outlet valves, the greater the flow capacity (Q). Furthermore, the larger the inlet and outlet valve openings, the lower the ring blower air flow pressure (P).